Evaluasi Tingkat Pelayanan pada Jalan Candi Panggung Kecamatan Lowokwaru Kota Malang - Eli , Elisabeth; Arifiato , Andy Kristafi ; Rahma , Pamela Dinar (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
Evaluation The high volume of traffic that passes through the Temple Road on the stage causes the meeting of vehicles that are quite dense from various directions of the road which results in a buildup of vehicles in every traffic jam during rush hour such as the morning when the community departs for activities, during the day and in the afternoon when the community returns home from their activities. The buildup of vehicles was caused by the large number of vehicles that passed, therefore research was carried out on these roads. As for this research a vehicle volume survey, side obstacle survey, and road geometry survey were then analyzed using the calculation method from the Indonesian Road Capacity Manual (MKJI, 1997). Based on the results of the analysis, the maximum volume on the Candi Panggung road segment is 2814 ken / hour and 1631.9 amp / hour with the occurrence of sidebarriers per 200 m / hour at peak hours on the Candi Panggung road at 14.6 SMP / hour. The saturation degree (DS) value on the Candi Panggung street based on the calculation result is 1.32smp / hour. The level of road service on Candi Panggung street is at the level ofservice F (very low).